Material de enseñanza de la biodiversidad Colombiana, basada en la analogía de la música vallenata y los cuentos tradicionales, dados en el corregimiento de los Monos, Municipio de Lorica Córdoba en la Institución Educativa Jesús de Nazareth para los estudiantes de los grados octavo y noveno. (2021)
As of Law 23 of 1973, under its application of Decree 2811 of December 18, 1974 (National Code of Renewable Natural Resources and Environmental Protection), in Colombia spaces of training, management and projection for the proper care of the environment, the concern of caring for biodiversity and natural resources is born through environmental education